Assessing the Need for Ecotourism Cluster Establishment in Georgia: Ways to Increase the Country’s Competitiveness - Khakhishvili, Tamar (European Scientific Journal, ESJ, 2020)
Georgia is famous for wine, hospitality, culture, and history at the international level. Before now, tourism in Georgia was only related to wine tourism and sea resorts, but in recent years, the country is positioning itself as an emerging destination for adventurous tourism. Industry potential is not fully utilized and it has more hidden possibilities to attract more visitors. This paper focuses on assessing the need for ecotourism cluster establishment in Georgia. In fulfilling this objective, a survey was conducted. Questionnaires were distributed to ecotourism service providers of the country. 54 managers of national parks and other protected areas (Lagodekhi Protected Areas, Kazbegi National Park, Martvili Canyon Natural Monument, Borjomi-Kharagauli National Park and Machakhela National Park) were chosen for the survey. The selected respondents are the managers of the most popular ecotourism destinations among Georgian and foreign ecoturists. Due to the various locations in different parts of Georgia, it took about two weeks to conduct the survey. The results of the survey showed that ecotourism industry representatives agree on the need of cluster establishment for more development of the field. The paper also demonstrated that building promising ecotourism industry through strong cluster development is directly related to increasing the country’s competitiveness.